Arus Baru Feminisme Islam Indonesia dalam Film Religi - Hakim, Lukman (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2013)
Abstract: This paper deals with Islamic feminism within the Indonesian religious moving picture Ketika Cinta Bertasbih 2 (KCB). Using semiotic approach, the study shows that the depiction of women’ lives in this film has a different way to the classical western film narrative structures which tend to explore women bodies as an object of masculine desire, as well as Indonesian religious (Islamic) films which commonly depict stereotypical portrayal of women as passive, inexpressive and dependent. Furthermore, this film can be considered as the representation of post-traditional Islam feminist, which seeks to deconstruct the ideology of the Javanese women through re-interpreting Islamic teachings in line with contemporary social realities and traditions.Keywords: religious film, woman representation, Islamic post-traditionalism, semiotics